Melanoma‐derived IL‐1 converts vascular endothelium to a proinflammatory and procoagulatory phenotype via NFκB activation. Issue 9 (September 2014) - Strozyk, Elwira A.; Desch, Anna; Poeppelmann, Birgit; Magnolo, Nina; Wegener, Joachim; Huck, Volker; Schneider, Stefan W.
Abstract Spreading of melanoma is associated with efficient extravasation of circulating tumor cells from the vascular system into distant target organs. This process is accompanied and supported by proinflammatory and procoagulatory conditions. In this study, we analysed the ability of human melanoma cell lines to activate endothelial cells (ECs) in vitro. Some melanoma cells, that is, MV3, were shown to trigger an prompt calcium‐flux‐dependent, procoagulatory endothelial response that was accompanied by luminal release of ultra‐large von Willebrand factor (ULVWF) fibres that were immobilized to the endothelial surface layer. In contrast to MV3‐derived supernatant, prolonged treatment of ECs with WM9‐derived supernatant mediated a pronounced activation of nuclear factor kappa B (NFκB). NFκB activation in ECs was dependent on both IL‐1α and IL‐1β secreted from melanoma cells. Melanoma‐derived IL‐1 mediated an upregulation of proinflammatory cytokines IL‐6 and IL‐8, the intercellular adhesion molecule‐1 (ICAM‐1), the vascular cell adhesion molecule‐1 (VCAM‐1) and the procoagulatory tissue factor (TF) in ECs. Our data show that melanoma cells activate ECs either directly and within seconds or by an IL‐1‐mediated NFκB activation. Both pathways of EC activation convert the regular repressive function of ECs on inflammation and coagulation to a proinflammatory and procoagulatory surface that supports tumor progression.